Impaired Mitochondrial Substrate Oxidation in Muscle of Insulin-Resistant Offspring of Type 2 Diabetic Patients - Befroy, Douglas E.; Petersen, Kitt Falk; Dufour, Sylvie; Mason, Graeme F.; de Graaf, Robin A.; Rothman, Douglas L.; Shulman, Gerald I. (Diabetes (New York, N.Y.), 2007)
Impaired Mitochondrial Substrate Oxidation in Muscle of Insulin-Resistant Offspring of Type 2 Diabetic Patients Douglas E. Befroy 1 , Kitt Falk Petersen 1 , Sylvie Dufour 2 , Graeme F. Mason 3 , Robin A. de Graaf 3 , Douglas L. Rothman 3 and Gerald I. Shulman 1 2 4 1 Department of Internal Medicine, Yale University School of Medicine, New Haven, Connecticut 2 Howard Hughes Medical Institute, Yale University School of Medicine, New Haven, Connecticut 3 Department of Diagnostic Radiology, Yale University School of Medicine, New Haven, Connecticut 4 Department of Cellular and Molecular Physiology, Yale University School of Medicine, New Haven, Connecticut Address correspondence and reprint requests to Gerald I. Shulman, MD, PhD, Howard Hughes Medical Institute, Yale University School of Medicine, The Anlyan Center, S269, P.O. Box 9812, New Haven, CT 06536-8012. E-mail: gerald.shulmanatyale.edu Abstract Insulin resistance is the best predictor for the development of diabetes in offspring of type 2 diabetic patients, but the mechanism responsible for it remains unknown. Recent studies have demonstrated increased intramyocellular lipid, decreased mitochondrial ATP synthesis, and decreased mitochondrial density in the muscle of lean, insulin-resistant offspring of type 2 diabetic patients. These data suggest an important role for mitochondrial dysfunction in the pathogenesis of type 2 diabetes. To further explore this hypothesis, we assessed rates of substrate oxidation in the muscle of these same individuals using 13 C magnetic resonance spectroscopy (MRS). Young, lean, insulin-resistant offspring of type 2 diabetic patients and insulin-sensitive control subjects underwent 13 C MRS studies to noninvasively assess rates of substrate oxidation in muscle by monitoring the incorporation of 13 C label into C 4 glutamate during a [2- 13 C]acetate infusion. Using this approach, we found that rates of muscle mitochondrial substrate oxidation were decreased by 30% in lean, insulin-resistant offspring (59.8 ± 5.1 nmol · g −1 · min −1 , P = 0.02) compared with insulin-sensitive control subjects (96.1 ± 16.3 nmol · g −1 · min −1 ). These data support the hypothesis that insulin resistance in skeletal muscle of insulin-resistant offspring is associated with dysregulation of intramyocellular fatty acid metabolism, possibly because of an inherited defect in the activity of mitochondrial oxidative phosphorylation. COX, cytochrome oxidase FID, free induction decay IMCL, intramyocellular lipid IRS-1, insulin receptor substrate-1 ISI, insulin sensitivity index MRS, magnetic resonance spectroscopy PDH, pyruvate dehydrogenase PGC, peroxisome proliferator–activated receptor-γ coactivator SDH, succinate dehydrogenase TCA, tricarboxylic acid Footnotes Published ahead of print at http://diabetes.diabetesjournals.org on 7 February 2007. DOI: 10.2337/db06-0783. The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “advertisement” in accordance with 18 U.S.C. Section 1734 solely to indicate this fact. Accepted January 31, 2007. Received July 6, 2006. DIABETES